T‐cell recognition is shaped by epitope sequence conservation in the host proteome and microbiome. Issue 1 (8th February 2016) - Bresciani, Anne; Paul, Sinu; Schommer, Nina; Dillon, Myles B.; Bancroft, Tara; Greenbaum, Jason; Sette, Alessandro; Nielsen, Morten; Peters, Bjoern
Summary: Several mechanisms exist to avoid or suppress inflammatory T‐cell immune responses that could prove harmful to the host due to targeting self‐antigens or commensal microbes. We hypothesized that these mechanisms could become evident when comparing the immunogenicity of a peptide from a pathogen or allergen with the conservation of its sequence in the human proteome or the healthy human microbiome. Indeed, performing such comparisons on large sets of validated T‐cell epitopes, we found that epitopes that are similar with self‐antigens above a certain threshold showed lower immunogenicity, presumably as a result of negative selection of T cells capable of recognizing such peptides. Moreover, we also found a reduced level of immune recognition for epitopes conserved in the commensal microbiome, presumably as a result of peripheral tolerance. These findings indicate that the existence (and potentially the polarization) of T‐cell responses to a given epitope is influenced and to some extent predictable based on its similarity to self‐antigens and commensal antigens.